ERROR ANALYSIS OF SENIOR HIGH SCHOOL STUDENTS IN SOLVING THE PROBLEMS OF STRAIGHT LINE ON THE COORDINATE PLANE - Bonaventura Wastu Sotyagung; Murdanu . (Universitas Negeri Yogyakarta, 2017)
Problem-solving ability is an ability that must be had by students to complete the issue of straight-line equation. The capability of understanding the concepts and settlement procedures is absolutely necessary. The low absorptive capacity on the national exam and the previous studies indicate the magnitude of the inability of the students to solve the problems of a straight-line topic. Therefore, an analysis of the student’s errors is needed to know the forms of the existing errors as a reference in the improvement of the learning.This study aims to determine the forms of errors made by the students in solving the problems of straight line on the coordinate plane. The errors of the completion were classified into the conceptual and procedural errors. The errors were assessed using the indicators of conceptual and procedural errors proposed by Kastolan. This research is a quantitative study. The instrument used was the essay test about the straight-line equation materials.The research resulted in the data of the forms of conceptual and procedural errors committed by the students in solving the problems of the essay test about the straight-line equation. The procedural errors found were in the forms of: a) errors in determining the formulas or theorems or definitions to solve a problem, made by 16,87% of students, b) the use of formulas, theorems, or definitions which did not match the prerequisite conditions for the application of them, made by 5,24% of students, and c) the absence of the formulas, theorems, or definitions of a problem, made by 30,77% of students. Meanwhile, the conceptual errors found were in the forms of: a) the steps of problem solving which were not hierarchically structured, made by 3,32% of students and b) an error or an inability to manipulate the steps to solve a problem, made by 48,25% of students.